How is music listening purpose related to stress recovery? – two preliminary studies in men and women - Song, Yichen; Mewes, Ricarda; Skoluda, Nadine; Nater, Urs M. (Frontiers in Psychology, 2023)
Studies have suggested that listening to music can reduce psychological and biological responses to a stressor. However, it is unclear whether music has the same effect on stress recovery. According to field studies, people commonly use music in daily life for the specific purpose of relaxation. We explored whether individuals who generally use music for relaxation purposes show improved recovery from an acute stressor. In two independent studies, twenty-seven healthy female participants (Mage = 24.07) (Study 1) and twenty-one healthy male participants (Mage = 23.52) (Study 2) were separated into two groups based on their frequency of using music for relaxation purposes (low vs. high). All participants underwent a lab-based psychosocial stress test. Subjective stress levels were measured using visual analogue scales. Salivary cortisol and salivary alpha-amylase were measured to assess endocrine and autonomic stress responses, respectively. Subjective stress levels and saliva samples were measured nine times throughout the stress induction and recovery procedure. Chronic stress levels were assessed using the Perceived Stress Scale and the Screening Scale of Chronic Stress. No significant differences were observed in subjective stress levels, salivary alpha-amylase activity, or cortisol concentration between the two groups in either of the two studies. Contrary to our expectations, the results indicate that habitual music listening for relaxation purposes is not associated with improved recovery from a stressor. Further analyses revealed that among male participants, increased use of music for relaxation purposes was related to more chronic stress levels (t(10.46) = 2.45, p = 0.03, r = 0.60), whereas female participants exhibited a trend in the opposite direction (t(13.94) = -1.92, p = 0.07, r = 0.46). However, due to the small sample size, future exploration is necessary to enhance the statistical power of the results of the study.